Ijime, Mentsu, dan LGBTQIA+ dalam Film Monster (2023): Kajian Hegemoni Gramsci - Fitria, Ajeng Aisyah; Priyatama, Ardian Nugraha (Vocational College of Diponegoro University, 2025)
Homogeneous Japan is the source of several problems that have yet to be solved, one of which is bullying. The amount of bullying that occurs, especially in schools, causes many students to be depressed and even commit suicide. These harmful things are then represented in a film titled Monster (2023). In this paper, there are two research questions, namely 1) how does the government dominate and hegemonise society so that the concept of homogeneity and mentsu can crystallise in Japan? 2) what is the relationship between the discourses of LGBTQIA+, ijime, and mentsu that appear in the film? Antonio Gramsci's theory of hegemony is used with a qualitative method to dissect the film. This research discovered that the film attempts to voice the discrimination received by LGBTQIA+ people in Japan by portraying them as two boys who fall in love and yearn for freedom. The societal pressure that considers them different due to the hegemony of the homogeneous concept of Confucianism leads to ijime. This is exacerbated by the mentsu in society, which has a reciprocal relationship. LGBTQIA+ people therefore have no space in conservative Japanese society and so the film was produced to emancipate freedom for subaltern LGBTQIA+ people.